2019
DOI: 10.1016/j.bbrep.2019.100636
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of thrombin, an unexplored function of retinoic acid

Abstract: Retinoic acid, a derivative of vitamin A, is known to possess in vivo anti-inflammatory, anti-platelet and fibrinolytic activities. We have investigated the in vitro thrombin and platelet aggregation inhibitory activities of vitamin A (retinol) and its derivatives, retinoic acid and retinaldehyde. The thrombin enzymatic assay was performed fluorimetrically to assess the inhibition of thrombin (Sigma and plasma). Retinoic acid, retinaldehyde and retinol exhibited po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In the present study, TNF-a concentration was significantly higher in the 13 cis retinoic acid group in comparison to the other group after 14 days of treatment.this agrees with a recent study, which included 522 COVID patients and 40 healthy controls from two hospitals in Wuhan, China, which showed a negative correlation between T cells numbers and the serum IL6, IL-10, and TNF-a concentration, on the other hand, patients in decline period showing reduced IL-6, IL-10, and TNF-a concentrations and restored T cell counts (9). Severe patterns of COVID-19 ARDS are characterized by thrombin burst and consequent coagulation activity(66).It was documented that retinoic acid significantly inhibit thrombin activity (65 ). This comes in agreement to our study, which revealed that thrombin activity significantly decreased in both groups, however, the reduction was significantly in the13 cis retinoic acid group than the other group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, TNF-a concentration was significantly higher in the 13 cis retinoic acid group in comparison to the other group after 14 days of treatment.this agrees with a recent study, which included 522 COVID patients and 40 healthy controls from two hospitals in Wuhan, China, which showed a negative correlation between T cells numbers and the serum IL6, IL-10, and TNF-a concentration, on the other hand, patients in decline period showing reduced IL-6, IL-10, and TNF-a concentrations and restored T cell counts (9). Severe patterns of COVID-19 ARDS are characterized by thrombin burst and consequent coagulation activity(66).It was documented that retinoic acid significantly inhibit thrombin activity (65 ). This comes in agreement to our study, which revealed that thrombin activity significantly decreased in both groups, however, the reduction was significantly in the13 cis retinoic acid group than the other group.…”
Section: Discussionmentioning
confidence: 99%
“…Severe patterns of COVID-19 ARDS are characterized by thrombin burst and consequent coagulation activity(66). It was documented that retinoic acid significantly inhibit thrombin activity (65). This comes in agreement to our study, which revealed that thrombin activity significantly decreased in both groups, however, the reduction was significantly in the13 cis retinoic acid group than the other group.…”
Section: Discussionmentioning
confidence: 99%
“…Retinol participates in regulation of trophic processes and increase of resistance of an organism to infections, stimulates growth and development of an organism, protein biosynthesis, glycoproteins, steroid hormones, influences metabolism of nucleic acids. In contrast, animals with Vitamin A deficiency have a decrease in ribosomal and transport RNA content (Chen et al, 2008;Erkelens & Mebius, 2017;Baishnikova et al, 2018;Krishna et al, 2019).…”
Section: Vitamin a And Reproductive Functionmentioning
confidence: 98%